2005
DOI: 10.1097/01.mlg.0000163744.89688.e8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Percutaneous Dilatational Tracheotomy: A Prospective Evaluation of 500 Consecutive Cases

Abstract: Endoscopic PDT is associated with a low complication rate and is at least as safe as surgical tracheotomy in the ICU setting. Bronchoscopy significantly decreases the incidence of complications and should be used routinely. While embraced by critical care physicians, endoscopic PDT has been infrequently performed by otolaryngologists. As the airway experts, otolaryngologists are in the best position to learn and teach the procedure as it should be done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
192
1
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(214 citation statements)
references
References 169 publications
(248 reference statements)
4
192
1
17
Order By: Relevance
“…Of all tracheotomies, 72.9% were performed in the first 3 weeks after endotracheal intubation (Table II). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The period of cannulation varied strongly (range, 1-730 days) (n ¼ 291). In 146 patients (49.5%), the cannula remained in situ for a time period between 1 week and 1 month (20.3% 1-7 days and 25.3% 30-90 days).…”
Section: Clinical Time Intervalsmentioning
confidence: 99%
“…Of all tracheotomies, 72.9% were performed in the first 3 weeks after endotracheal intubation (Table II). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The period of cannulation varied strongly (range, 1-730 days) (n ¼ 291). In 146 patients (49.5%), the cannula remained in situ for a time period between 1 week and 1 month (20.3% 1-7 days and 25.3% 30-90 days).…”
Section: Clinical Time Intervalsmentioning
confidence: 99%
“…4,5 However, bronchoscopy does not identify the vascular structures or the thyroid gland in the neck region and thus does not prevent complications linked to local organ lesions (punctured vessels or a punctured thyroid) and in patients with acute brain injury, it can cause acute elevations in intracranial pressure. Preliminary reports suggest that sonographic delineation of anatomy prior to tracheal puncture during PT may help prevent bleeding from pre-tracheal vascular structures and placement of the tracheal tube above the first tracheal ring.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that PCT should be automatically contraindicated in these groups of patients. 5,9 Many of the patients in our series had one of these factors: obesity in 15 patients (including one patient with BMI 55.9 kg/m 2 ) and cervical spine precautions in 8 patients. Nine of the obese patients who underwent USPCT in comparison to 6 BPCT had no incidence of any complication while all the six undergoing BPCT had complications (4 tracheal cuff puncture, 3 had hypoxia while 2 had moderate bleeding).…”
mentioning
confidence: 95%
“…2,3 Despite the lack of any randomized controlled trials, proponents of continuous bronchoscopy claim that it may prevent major complications 4 such as misplacement of the tracheostomy tube and posterior tracheal wall laceration. A retrospective review found no difference in PDT complications with or without bronchoscopy.…”
Section: To the Editormentioning
confidence: 99%